Faktor-Faktor yang Berhubungan dengan Asfiksia Neonatus: Studi Kasus Kontrol di RSUD Kabupaten Serang, Banten, Indonesia - Khotimah, Husnul; Khasanah, Yosi Yusrotul; Arofah, Nur (Jurnal Epidemiologi Kesehatan Indonesia, 2024)
Asphyxia in newborns is a common and serious cause of neonatal morbidity and mortality nationally and internationally. Risk factors for asphyxia can be seen from maternal and infant factors. The purpose of this study was to determine the risk factors in mothers and infants and to analyze which factors have the most influence on asphyxia. This study is a quantitative analytical study with a case-control approach. The number of case samples was 53 infants who experienced asphyxia and 53 control (1:1) infants so that the total sample was 106 infants. The variables studied were parity, Low Birth Weight (LBW), preeclampsia, and Premature Rupture of Membranes (PROM). Bivariate data analysis used chi square and multivariate data analysis used multiple logistic regression. The association value measured was the adjusted odds ratio (AOR), where AOR> 1 was interpreted as a risk. An increased risk was found in parity 1 and > 4 (AOR 3.824; 95% CI 1.220-11.994), LBW (AOR 11.726; 95% CI 3.282-41.898), preeclampsia (AOR 24.498; 95% CI 5.604-107.098), and PROM (AOR 18.821; 95% CI 4.377-80.928) with neonatal asphyxia. The dominant factor influencing neonatal asphyxia was preeclampsia with a value of 24.498 (AOR 24.498; 95%CI; 5.604-107.098), meaning that infants with a history of maternal preeclampsia had a 24 times greater chance of experiencing neonatal asphyxia compared to those without preeclampsia. There is an urgent need to develop strategies for early identification and management of birth asphyxia involving beneficiaries, health professionals and policy makers. Health workers should be trained to perform emergency obstetric care especially management of preeclampsia, LBW, PROM.